IMPROVING BONE DENSITY BY USING VERSAH BURS IN ORAL IMPLANTOLOGY - Florin Ciprian Badea; Aureliana Caraiane; Doriana Agop Forna; Gheorghe Raftu (Romanian Society of Oral Rehabilitation, 2023)
The aim of the study is to demonstrate the change in bone tissue density by using osteocondensation burs. An important factor that influences the long-term prognosis of the dental implant is the bone density; therefore, any method of optimizing the bone tissue is important for achieving the primary stability of the dental implant.The basis for osseointegration, leading to permanent, functional and interactive, coexistence between titanium and bone, is established when a topographically harmonious and precise recipient site - geometrically adjusted to the anatomy of the fixture - is gently prepared in bone.For these reasons, any way to optimize the density of the bone tissue is important from the point of view of achieving the primary stability of the dental implant.The working hypothesis of this study is that the use of osteocondensation burs can improve the quality of bone tissue in terms of density. Material and method. The study was carried out on a group of 20 patients in whom Medical System Implants (MSI) dental implants were inserted as follows: 10 patients in whom MSI dental implants were inserted using the kit of this implant system and 10 patients in whom MSI dental implants were inserted using the osteocondensation kit. Results. . In 7 of the 10 patients in whom osteocondensation burs were used, the density of the bone tissue changed from D5-D4 (4 patients), D4-D3 (3 patients). Conclusions.Within the limits of the studied group, it can be seen that this method comes before the clinician in the conditions where the patient has a large amount of cancellous bone tissue. The use of these burs prevents peri-implant type complications by optimizing osseointegration.